PROTECTING PATIENTS FROM VENTILATOR-ASSOCIATED PNEUMONIA: CRITICAL CARE NURSES' ESSENTIAL ROLE - Fatimah Ali Hakami , Amira Mohammed Abdulrahman Alharthi, Malikah Mohammed Hathal, Al-anazi,saeed Marzook Janpan,romoz Badi Alharbi,naif Mohammad Almutairi, Shujun Ahmad Khiry, Ahmad Jarallah Altuwayhir, Moused Marzouq H Almoused, ,; Najla Abdullah Barzig, Aliah abdullah Barzig, Tarfah Samah Aldhfeeri, Ahlam Abdullah Al Ghawas, Gays Obaid Al Otaibi, Amnah Hameed Alazmi, (Chelonian Research Foundation, 2022)
One of the most common nosocomial infections among ventilated patients in intensive care units (ICUs) is ventilator-associated pneumonia (VAP), which is linked to an increase in ICU stay days, morbidity, and mortality. Every hospital is highly concerned about preventing it. The majority of treatments and preventative techniques are incorporated into standard nursing care. In order to avoid VAP, nurses play a variety of crucial tasks, including those of care manager, educator, coordinator, and evaluator. Following evidence-based recommendations for preventing ventilator-associated pneumonia may be hampered by nurses' ignorance about infection prevention and appropriate nursing care. In order for nurses to apply their knowledge in clinical practice, this study will assist them gain a thorough understanding of VAP and how to prevent it. Comprehending the pathophysiology, risk factors, and care package of VAP is crucial for effective prevention and management of the condition. Every ICU needs to have defined procedures, plans of action, and ongoing monitoring with reference to the care bundle. Keywords: ICU, nurses, critical care, ventilator-associated pneumonia (VAP), risk factors.